2009
DOI: 10.1590/s1807-59322009000300004
|View full text |Cite
|
Sign up to set email alerts
|

Significant Performance Variation Among PCR Systems in Diagnosing Congenital Toxoplasmosis in São Paulo, Brazil: Analysis of 467 Amniotic Fluid Samples

Abstract: INTRODUCTION Performance variation among PCR systems in detecting Toxoplasma gondii has been extensively reported and associated with target genes, primer composition, amplification parameters, treatment during pregnancy, host genetic susceptibility and genotypes of different parasites according to geographical characteristics. PATIENTS A total of 467 amniotic fluid samples from T. gondii IgM- and IgG-positive Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 28 publications
8
42
2
6
Order By: Relevance
“…These data are consistent with a recent Brazilian study conducted by Okay et al 21 In addition, previous studies have also shown high sensitivity and specifi city for markers designed to amplify different regions of the B1 gene in clinical samples. 13,18,19,25,27,29 Other studies conducted using European clinical samples aiming to compare sensitivities of both DNA regions have shown that those from repeat regions were more sensitive than those from the B1 gene.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These data are consistent with a recent Brazilian study conducted by Okay et al 21 In addition, previous studies have also shown high sensitivity and specifi city for markers designed to amplify different regions of the B1 gene in clinical samples. 13,18,19,25,27,29 Other studies conducted using European clinical samples aiming to compare sensitivities of both DNA regions have shown that those from repeat regions were more sensitive than those from the B1 gene.…”
Section: Resultssupporting
confidence: 92%
“…[12][13][14][17][18][19][20] The majority of these studies aiming to compare sensitivities of both DNA regions were conducted in European clinical samples, but little research has been done on Brazilian samples. 21 These data, combined with certain limitations in laboratorial practices, such as the low parasite levels in some clinical samples, lead us to compare two molecular markers directed at the B1 gene and the 529-bp sequence for cerebral toxoplasmosis diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent Brazilian study (23) reported a lower proportion of positive amniotic fluids with the REP-529 target than with B1 (36.5% and 87.3%, respectively), with only 23.8% of samples being positive with both targets. This unusual finding must be verified on other series of clinical samples from South America to check if atypical parasite strains circulating in this area might lack the REP-529 sequence or have mutations or modifications in the number of repetitions that might lead to a decreased sensitivity of this PCR target, which now appears to be the gold standard for European parasite strains.…”
Section: Discussionmentioning
confidence: 87%
“…In these patients, PCR applied to peripheral blood specimens could eliminate the requirement for invasive CNS biopsy techniques (429). A number of PCR assays have also been optimized for use on amniotic fluid for the diagnosis of congenital toxoplasmosis (188,404,409). As mentioned above in the section on pregnancy, primary Toxoplasma infections acquired prior to the commencement of a pregnancy pose little threat to the fetus.…”
Section: Toxoplasma Gondiimentioning
confidence: 99%